The Effect of Innovation, Promotion, and Quality of Products on Consumer Loyalty with Satisfaction as Intervening Variables (Case Study Costumer PT. Mandom In Surabaya) - Rega Irsa Irawan; Sengguruh Nilowardono (Quantitative Economics and Management Studies, 2021)
This study aims to determine the effect of innovation, promotion, product quality on consumer loyalty with customer satisfaction as intervening. This research method uses quantitative with OLS analysis tools. The research instrument was a questionnaire with 75 samples of Gastby product consumers. The results of the study prove that Innovation has positive significant effect on consumer satisfaction as evidenced by the results of t value of 4.457 with p-value of 0.00, Innovation has significant positive effect on consumer loyalty as evidenced by the results of t value of 8.897 with p-value amounting to 0,000, promotion does not have a significant positive effect on customer satisfaction t value of 0.421 with a p-value of 0.674, promotion does not have a significant positive effect on consumer loyalty as evidenced by the result of t of 1,277 with a p-value of 0,202, quality the product has significant positive effect on customer satisfaction as evidenced by the results of t table (1.666) and p-value smaller than 0.05, product quality has significant positive effect on loyalty consumer as evidenced by the results of this value greater than t table (1.666 ) and p-value is smaller than 0.05 consumer power has an effect on consumer loyalty as evidenced by the results of t value of 4.689 with a p-value of 0.00.